TURKS AND JEWS: HISTORICAL, LINGUISTIC, AND CULTURAL CONNECTIONS (Лучшие интеллектуальные исследования, 2025)
Turks and Jews are two ancient peoples whose contributions have profoundly shaped human civilization. Despite their geographic and historical differences, their languages, cultures, and values reveal deep connections rooted in shared philosophical, religious, and cultural frameworks. Unlike Arabs, Turks, including modern Uzbeks, use the term Ilohim alongside Allah when referring to God, a practice that underscores their unique cultural and linguistic affinity with Jewish traditions.